ANALISIS PERBANDINGAN PENDAPATAN USAHATANI KELAPA SAWIT SEBELUM DAN PASCA COVID-19 DI DESA GEMA KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Wanda Muzekri; Ujang Paman (UIR Press, 2023)
Oil palm farming is the main source of economy in Gema Village, and the crop is continuously cultivated after Covid-19. This study aims to analyze the characteristics of farmers and farming profiles; costs, production, income, and efficiency of oil palm farming post Covid-19; and income comparison of oil palm farming before and after Covid-19. The method used was a survey and the research was conducted in Gema Village, Kampar Kiri District, Kampar Regency, Riau Province. The research was carried out for 6 months, starting from January to June 2023. A total of 30 farmers were taken as respondents by a census. The data used in this research consisted of primary and secondary data. The data were analyzed by quantitative and qualitative descriptive techniques. The results showed that the average age of oil palm farmers was 44.87 yr, the length of education was 9 years, 12.3 years of experience, and 5 family members. The oil palm farm area ranged from 1 to 8 ha with an average of 3.09 ha. From the oil palm farm analysis, the average cost was Rp. 9,902,842/ha/yr before Covid-19 and Rp. 11,197,013/ha/yr after Covid-19. The gross income received before Covid-19 was Rp.17,942,825/ha/yr and after Covid-19 it was Rp.30,016,544/ha/yr. The net income received by farmers was Rp. 8,052.983/ha/yr before Covid-19 and Rp. 8,819,531/ha/yr after Covid 19, with an efficiency of 1.81 and 2.68 before and after Covid-19, respectively. It was found that oil palm farming income had a significant difference between before and after Covid-19.